The Letters of Marshall McLuhan and Pierre Elliott Trudeau: Privacy/Private Matters - Elaine Kahn (Laws, 2021)
There has been a paradigm shift in global communications since the death many years ago of prominent Canadians Marshall McLuhan and Pierre Elliott Trudeau. The correspondence between the two friends, from 1968 to 1980, presciently touched on our contemporary wired global village and the challenges it presents to personal privacy and to freedom of expression. I examine the relationship between the two men, as laid out in their letters and, to a lesser extent, in secondary sources, highlighting matters of privacy and media. Privacy hovers over the correspondence, even when it is not the stated topic. McLuhan, who is credited with the term “global village”, discussed with Trudeau the effect of new media on people’s notions of tribe and identity and privacy. Proving a direct influence from one man to the other, in either direction, is not possible, but there is much to play with. The gap is, as McLuhan often said, “where the action is”.